Existential alienation among the poets of the sixties - Adulhassan, Mutaz; Abbas , Hayder (Al-Adab Journal, 2025)
Existentialism is closely linked to man and thought, and this was a reason for the interest of studies related to it, as it was the focus of philosophers, writers, and all those working in fields related to thought, and the term existentialism is one of the terms produced by the philosophies of modernity that called for striking centralities, and focusing on man, his subjectivity, and his active presence in society; because man is the only being who is aware of the truth of his existence and interacts with the surrounding society negatively and positively, and the most important thing that distinguishes existentialism is also its opposition to the dominant forces that deprive the individual of freedom; as it created a qualitative shift in European thought during the mid-twentieth century, and this shift was represented in the call for change and renewal in the values ​​and ideals that restricted freedoms, so it was a reaction to the grand narratives that narrowed the borders on man and bestowed upon the self a freedom that allowed it to seize areas of life